Exergoeconomic optimization of liquid air production by use of liquefied natural gas cold energy. (15th September 2020) - Park, Jinwoo; Qi, Meng; Kim, Jeongdong; Noh, Wonjun; Lee, Inkyu; Moon, Il
Abstract: Exergoeconomic optimization of the production of liquid air by utilizing the cold energy of liquefied natural gas (LNG) was undertaken for the first time. LNG cold energy, which is generally wasted in commercial regasification, can potentially be harnessed to produce liquid air. By using an exergoeconomic approach, the optimal design for reducing the specific energy consumption in the production of liquid air was determined, affording a 7.45% reduction in the specific energy consumption. Thermodynamic analysis revealed that the specific energy consumption could be minimized by using the optimized portion of LNG cold energy. Economic study indicated that the optimized system also afforded a 4.61% reduction in the total cost. Beyond this, the effects of both increasing and decreasing the energy recovery operations were investigated, from which the most cost effective process flow was determined. In conclusion, the most cost effective strategy for reducing the specific energy consumption for liquid air production does not necessarily require using the largest proportion of LNG cold energy. This is because although adding equipment reduces the energy consumption, it also increases the total costs beyond an optimal point. These are important findings for advancing the effort to efficiently utilize LNG cold energy. Highlights: Exergoeconomic aspects were revealed for liquid air production via LNG cold energy. The use of LNG cold energy was optimized for more efficient liquid air production. Cost based optimum was found as function of the number of energy recovery stages. Optimization gave reductions of 7.45% in the energy required and 4.61% total cost.